Pendidik di RA Tazakka memegang Pembelajaran sentra berbasis Karakter: Peran pendidik dalam membangun anak Sholih Sholihah yang Berakhlaq Islami di RA Tazakka – Sawojajar - Tantya, Lailya Aries (Maliki Interdisciplinary Journal, 2024)
This study aims to examine the role of educators in character-based center learning in RA Tazakka - Sawojajar, with a focus on the formation of sholih sholihah children with Islamic morals. A qualitative approach is used with observation, interview, and documentation methods to collect data. The results of the study show that educators play an important role in instilling Islamic values into every aspect of central learning. Through structured and character-centered activities, such as Islamic stories, worship practices, and social activities, educators succeed in cultivating noble morals in children. The support of the school environment and the active involvement of parents also contribute significantly to the success of the formation of children’s character. This research emphasizes the importance of collaboration between educators, schools, and families in building the next generation with noble morals in accordance with Islamic values.